A Systems Approach to Sustainable Technical Product Design. - Luthe, Tobias; Kägi, Thomas; Reger, Jan (Journal of Industrial Ecology, 2013)
Many existing methods for sustainable technical product design focus on environmental efficiency while lacking a framework for a holistic, sustainable design approach that includes combined social, technical, economic, and environmental aspects in the whole product life cycle, and that provides guidance on a technical product development level. This research proposes a framework for sustainable technical product design in the case of skis. We developed a ski under the Grown brand, benchmarked according to social, environmental, economic, and technical targets, following an initial sustainability assessment, and delivered the first environmental life cycle assessment (ELCA) and the first social life cycle assessment (SLCA) of skis. The framework applies a virtual development process as a combination of ELCA to calculate the environmental footprint as carbon equivalents of all materials and processes and a technical computer-aided design (CAD) and computer-aided engineering (CAE) simulation and virtual optimization using parameter studies for the nearly prototype-free development of the benchmarked skis. The feedback loops between life cycle assessment (LCA) and virtual simulation led to the elimination of highly energy intensive materials, to the pioneering use of basalt fibers in skis, to the optimization of the use of natural materials using protective coatings from natural resins, and to the optimization of the production process. From an environmental perspective, a minimum 32% reduction in carbon equivalent emissions of materials in relation to other comparably performing skis has been achieved, as well as a pioneering step forward toward transparent communication of the environmental performance by the individual, comparable, and first published ski carbon footprint per volume unit.